How a dc Electric Field Drives Mott Insulators out of Equilibrium - Diener, P. (2018)
Out of equilibrium phenomena are a major issue of modern physics. In particular, correlated materials such as Mott insulators experience fascinating long-lived exotic states under a strong electric field. Yet, the origin of their destabilization by the electric field is not elucidated. Here we present a comprehensive study of the electrical response of canonical Mott insulators GaM4Q8 (M=V, Nb, Ta, Mo; Q=S, Se) in the context of a microscopic theory of electrical breakdown where in-gap states allow for a description in terms of a two-temperature model. Our results show how the nonlinearities and the resistive transition originate from a massive creation of hot electrons under an electric field. These results give new insights for the control of the long-lived states reached under an electric field in these systems which has recently open the way to new functionalities used in neuromorphic applications.